Genital examination training: assessing the effectiveness of an integrated female and male teaching programme. Issue 1 (December 2016) - McBain, Lynn; Pullon, Susan; Garrett, Sue; Hoare, Kath
Abstract Background Learning to undertake intimate female and male examinations is an important part of medical student training but opportunities to participate in practical, supervised learning in a safe environment can be limited. A collaborative, integrated training programme to provide such learning was developed by two university teaching departments and a specialist sexual health service, utilising teaching associates trained for intimate examinations in a simulated clinical educational setting. The objective of this research was to determine changes in senior medical students' self- reported experience and confidence in performing male and female genital examinations, before and after participating in a new clinical teaching programme. Methods A quasi-experimental mixed methods design, using pre and post programme questionnaires and focus groups, was used to assess the effectiveness of the programme. Results The students reported greatly improved skill, confidence and comfort levels for both male and female genital examination following the teaching programme. Skill, confidence and comfort regarding male examinations were rated particularly low on the pre-teaching programme self- assessment, but post-programme was rated at similar levels to the female examination. Conclusions This integrated female–male teaching programme (utilising trained teaching associates as simulated patients in a supervised clinical teaching environment) was successful in increasing senior medical students' skills and levels of confidence in performing genital examinations. There were differences between female and male medical students in their learning. Suggestions for improvement included providing more detailed instruction to some clinical supervisors about their facilitation role in the session.